The Effects of Early Marriage in Selected Barangays of Datu Saudi-Ampatuan Municipality, Maguindanao Province - Ansare K. Unos; Mohammad Rayyan B. Calib (Randwick International of Social Science Journal, 2022)
This study sought to explore the effects and challenges of early marriage in the selected barangays (Elian, Dapiawan, and Kitango) of Datu Saudi Ampatuan Municipality, Maguindanao Province. The researchers used the mixed research method which combines quantitative and qualitative methods in the same study. The respondents were 40 males and 40 females who have been married at their early age and currently living in the municipality. The following were the findings of the study: The overwhelmingly majority of the respondents agreed that early marriage is being practiced in accordance with the Shari‘ah Law, complying with the essential requisites of marriage in Presidential Decree 1083 or PD 1083. Meanwhile, 15% from the male respondents and 3% from the female respondents have admitted that there are disagreements that happened before the wedding commonly because of disapproval of their mother but easily resolve and facilitated. Majority of the respondents confirmed that the transaction between offer (ijab) and acceptance (qabul) duly witnessed by two competent persons after the guardian in marriage (wali) has given his/her consent. Large majority of the respondents also agreed that the “mahr” (dower) was given before the wedding and the female respondents were satisfied with the amount of the “mahr”. The researchers stated their recommendations addressed towards the Bangsamoro Autonomous Region in Muslim Mindanao (BARRM), local government units (LGUs), Barangay officials, and the academic community, to formulate or create program interventions like adult literacy, financial literary, and livelihood for those illiterate couple and other less fortunate individuals.